Clinical Characteristics and Long-term Follow-up of Ketosis-prone Diabetes in Thai Patients - Yotsapon, T.; Sarat, S. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Introduction: Diabetes presenting with ketoacidosis is a heterogeneous disorder. The purpose of this study was to determine whether ketosis-prone diabetes (KPDM) in Thai patients were different from type1 diabetes by assessment of the beta-cell response to a standardized mixed meal and pancreatic autoantibodies.Material and Methods: 20 patients who were categorized as ketosis-prone diabetes based on the occurrence of unprovoked DKA after the age of 30 years were compared with 12 type1 diabetic patients. The beta-cell function and pancreatic autoantibodies were followed after resolution of DKA every 6 months for 2 years.Results: Mean (±SD) age at presentation was 38.8±11.5 and 26.7+10.3 years in KPDM and type1 DM, respectively (p<0.05). Median (IQR) fasting plasma C-peptide obtained after resolution of DKA within 2 weeks was 0.90 ng/dl (0.20–1.30) in KPDM compared with 0.10 ng/dl (0.10–0.45) in type1 diabetes and median peak stimulated plasma C-peptide was 6.80 ng/dl (0.90–9.80) compared with 0.10 ng/dl (0.10–0.75). Based on Aβ classification, 4 patients were classified as A+β−, 12 patients were classified as A−β+, and 4 patients were classified as A−β−. No patient was classified as A+β+ in this study. At the median time of 31 months follow-up (range from 8–44 months), 11 patients from 12 A−β+ KPDM (92%) could be withdrawn from insulin treatment successfully at median time of 5 months after admission.Conclusions: Thai KPDM patients had variable clinical course which were different from typical type1 DM. The Aβ classification was proven to be useful predictors for consideration of insulin withdrawal after resolution of DKA.
Keywords: ketosis-prone diabetes; mixed meal tolerance test; long-term follow-up